Physical fitness spurts in childhood: a study in boys - Pereira, Sara (2021)
This study aimed to (1) estimate age-at-mid-growth spurt (age-at-MGS) in Portuguese boys from two different regions—the Azores islands and Viana do Castelo, and (2) identify spurts in a variety of physical fitness (PF) components aligned by age-at MGS in the two samples. A total of 176 (Azores, n = 91; Viana do Castelo, n = 85) boys aged 6 years old were followed annually to 10 years of age. Age-at-MGS and spurts in PF components (speed, explosive muscular strength, abdominal muscular strength, agility, and flexibility) were identified for each sample. The timing and intensities of the spurts were estimated using a non-smooth mathematical proce dure. In Azorean boys, age-at-MGS occurred at 7.8 years (6.99 cm y−1), whereas in Viana do Castelo it occurred at 7.9 years (6.20 cm y−1). Spurt in speed was at tained 12 months after the MGS in both samples (0.53 and 0.35 cm y−1 in Azores and Viana do Castelo, respectively), whereas spurts in explosive muscular strength and flexibility occurred 12 months before the MGS and at the MGS (Azores: 21.59 and 5.52 cm y−1 and Viana do Castelo: 14.12 and 2.5 cm y−1, respectively). Agility and abdominal muscular strength peaked between 0 and 12 months after the MGS (Viana do Castelo: 0.37 m s−1 y −1 and 6.71 reps y−1 and Azores: 0.28 m s−1 y −1 and 19.36 reps y−1, respectively). Results indicate that developmental spurts in explosive strength and flexibility occur before, or are coincident with, the mid-growth spurt in height, whereas spurts in speed, agility, and abdominal muscular strength occur after, or coincident with, the mid-growth spurt in height.